Dual oxidase 1 and NADPH oxidase 2 exert favorable effects in cervical cancer patients by activating immune response - Sang Yeon Cho; Sungha Kim; Mi-Ju Son; Gwanghun Kim; Parul Singh; Ha Neul Kim; Hei-Gwon Choi; Heon Jong Yoo; Young Bok Ko; Byung Seok Lee; Hyuk Soo Eun (BMC Cancer, 2019)
Abstract Background Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-derived reactive oxygen species (ROS) not only can promote cancer progression, but also they have recently emerged as mediators of the mucosal immune system. However, the roles and clinical relevance of the collective or individual NADPH oxidase (NOX) family genes in cervical cancer have not been studied. Methods We investigated the clinical significance of the NOX family genes using data from 307 patients with cervical cancer obtained from The Cancer Genome Atlas. Bioinformatics and experimental analyses were performed to examine NOX family genes in cervical cancer patients. Results Dual Oxidase1 (DUOX1) and Dual Oxidase 2 (DUOX2) mRNA levels were upregulated 57.9- and 67.5-fold, respectively, in cervical cancer patients. The protein expression of DUOX1, DUOX2, and NOX2 also identified in cervical squamous cell carcinoma tissues. Especially, DUOX1 and DUOX2 mRNA levels were significantly increased in patients infected with human papillomavirus (HPV) 16. Moreover, high DUOX1 mRNA levels were significantly associated with both favorable overall survival and disease-free survival in cervical cancer patients. High NOX2 mRNA levels was significantly associated with favorable overall survival. Gene set enrichment analyses revealed that high DUOX1 and NOX2 expression was significantly correlated with the enrichment of immune pathways related to interferon (IFN)-alpha, IFN-gamma, and natural killer (NK) cell signaling. Cell-type identification by estimating relative subsets of known RNA transcript analyses indicated that the fraction of innate immune cells, including NK cells, monocytes, dendritic cells, and mast cells, was elevated in patients with high DUOX1 expression. Conclusions DUOX1 and NOX2 expression are associated with mucosal immunity activated in cervical squamous cell carcinoma and predicts a favorable prognosis in cervical cancer patients.